Advances of curcumin in nervous system diseases: the effect of regulating oxidative stress and clinical studies - Wei, Yuxun; Li, Hong; Li, Yue; Zeng, Yue; Quan, Tian; Leng, Yanen; Chang, En; Bai, Yingtao; Bian, Yuan; Hou, Yi (Frontiers in Pharmacology, 2024)
In recent years, researchers have highly observed that neurological disorders (NSDs) with the aging of the population are a global health burden whose prevalence is increasing every year. Previous evidence suggested that the occurrence of neurological disorders is correlated with predisposing factors such as inflammation, aging, and injury. Particularly, the neuronal cells are susceptible to oxidative stress, leading to lesions caused by high oxygen-consuming properties. Oxidative stress (OS) is a state of peroxidation, which occurs as a result of the disruption of the balance between oxidizing and antioxidizing substances. The oxidative intermediates such as free radicals, hydrogen peroxide (H2O2), and superoxide anion (O 2 -) produced by OS promote disease progression. Curcumin, a natural diketone derived from turmeric, is a natural antioxidant with a wide range of neuroprotective, anti-inflammatory, anti-tumor, anti-aging, and antioxidant effects. Fortunately, curcumin is recognized for its potent antioxidant properties and is considered a promising candidate for the prevention and treatment of neurological diseases. Consequently, this review elucidates the mechanisms by which curcumin mitigates oxidative stress and emphasizes the potential in treating nervous system disorders, including depression, Alzheimer's disease, Parkinson's disease, epilepsy, subarachnoid hemorrhage, and glioblastoma. We aim to provide a new therapeutic option for the management of neurological diseases.